2015
DOI: 10.3389/fpsyg.2015.00730
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive training for delusions (MCTd): effectiveness on data-gathering and belief flexibility in a Chinese sample

Abstract: Metacognitive training (MCT) was developed to promote awareness of reasoning biases among patients with schizophrenia. While MCT has been translated into 31 languages, most MCT studies were conducted in Europe, including newer evidence recommending an individualized approach of delivery. As reasoning biases covered in MCT are separable processes and are associated with different symptoms, testing the effect of selected MCT modules would help to develop a targeted and cost-effective intervention for specific sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 82 publications
(103 reference statements)
1
33
1
Order By: Relevance
“…It is probable that this inconsistency is due to selective floor effects in the MCT+ group: As shown in Tables 1 and 2, the randomization process resulted in differences between the two groups regarding baseline symptoms, which were lower in MCT+ patients -and, in fact, lower than in previous studies by our group (Moritz et al, 2013a;Moritz et al, 2011) and others (Favrod et al, 2014;So et al, 2015). This, in combination with the rapid improvement, led to very low symptom levels in these patients post-intervention, while the control group may have benefited from greater margins for change.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…It is probable that this inconsistency is due to selective floor effects in the MCT+ group: As shown in Tables 1 and 2, the randomization process resulted in differences between the two groups regarding baseline symptoms, which were lower in MCT+ patients -and, in fact, lower than in previous studies by our group (Moritz et al, 2013a;Moritz et al, 2011) and others (Favrod et al, 2014;So et al, 2015). This, in combination with the rapid improvement, led to very low symptom levels in these patients post-intervention, while the control group may have benefited from greater margins for change.…”
Section: Discussionmentioning
confidence: 39%
“…Previous studies have shown that use of MCT material in an individual treatment format can have beneficial effects on cognitive biases and/or delusions after very few sessions (Balzan et al, 2014;Balzan and Galletly, 2015;Ross et al, 2011;So et al, 2015;Waller et al, 2011). In a randomized, controlled, rater-blind trial of group MCT combined with individualized sessions (Moritz et al, 2011), patients in the MCT arm showed significantly greater improvement in delusion severity and conviction, as well as in jumping-to-conclusions, relative to the active control group.…”
Section: Introductionmentioning
confidence: 99%
“…We have checked the baseline data of the studies on delusions. The three studies with the highest baseline delusion scores were So et al (2015), and van Oosterhout et al (2014). Taking these three studies, the effect size is 0.49, while studies with the lowest delusion scores at baseline (Moritz et al 2011a(Moritz et al ,b, 2013Briki et al 2014;Gaweda et al 2015) have a pooled effect size of 0.25 on delusions.…”
Section: Evolution Of Mctmentioning
confidence: 99%
“…In their introduction (Moritz et al 2011) refer to another meta-analysis by Jiang et al (2015) quoting significant effects for positive symptoms (as well as for delusions without the study by van Oosterhout et al 2014). The van Oosterhout et al (2014) study is a negative study, but it is the largest randomized controlled trial (RCT) and indeed was rated as the study with the lowest risk of bias by Jiang et al; it is not clear why one would discard the best study to date?…”
mentioning
confidence: 99%
See 1 more Smart Citation